Pengabdian Masyarakat Dalam Peningkatan Sumber Daya Manusia di Desa Kerinci Kanan - Melda Sundari; Nuraini N; Muhammad Yahya; Masayu Adara Raditya; Indah Azhari; Irfan Izaz Asraf; Atmatul Fitri; Ana Luthfia Anggraini; Muhammad Harry Satria; Utami Pratiwi Indra (Yayasan Daarul Huda Kruengmane, 2023)
In this KKN program we have realized one of the Tri Dharmas of Higher Education, namely community service. Apart from realizing one of the Tri Dharmas of Higher Education, we also try to implement one of the functions of the students themselves, namely agent of change. We have implemented many activity programs in Kerinci Kanan Village. These activity programs cover the education sector by providing socialization to schools, then also helping them learn subjects at school at both elementary school level, the social sector by participating in socialization and posyandu activities, gymnastics, participating in mutual cooperation activities, wirid activities, joining together. MTQ parade activities, visiting duck farms and religious activities such as group Koran recitation activities, training children in the call to prayer and bilal as well as participating in various activities held in Kerinci Kanan Village to celebrate Indonesian independence day. The aim of implementing this program is that it is hoped that students, namely ourselves, can gain learning experience through direct involvement in society. Find, formulate, solve and overcome various problems in the field. The target of our activities is the entire community in Kerinci Kanan Village, whether they are children, youth or parents.